It is not boring in Barnoldswick! The case of the Barnoldswick water supply borehole in northern England, and what should, could, and has been done to celebrate the borehole core. (30th January 2023) - Murphy, Phil; Kabrna, Paul
Abstract : The importance of borehole cores and the geological insights which they provide are often underappreciated. Here the problems of seeking a water supply for an industrial town in Northern England have resulted in a very rare opportunity to view a core in the public domain. As we need to raise the profile of the geosciences and ensure a public understanding of the importance of geology in underpinning our society we should seek other opportunities to highlight history and importance of borehole drilling and the cores recovered.